If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x-3-(23x-48)+(x+93)=58x-(24x-44)+6
We simplify the equation to the form, which is simple to understand
12x-3-(23x-48)+(x+93)=58x-(24x-44)+6
Remove unnecessary parentheses
12x-3-23x+48+(x+93)=58x-(24x-44)+6
Remove unnecessary parentheses
+12x-3-23x+48+x+93=+58x-(+24x-44+)+6
Remove unnecessary parentheses
12x-3-23x+48x+93=58x-24x+44+6
We move all terms containing x to the left and all other terms to the right.
+12x-23x+1x-58x+24x=+44+6+3-48-93
We simplify left and right side of the equation.
-44x=-88
We divide both sides of the equation by -44 to get x.
x=2
| 5x/2= | | 12x^3y+104x^2y-36xy=0 | | 2/3+5c=-8 | | 5x^2+100x+3=0 | | x^2+x+3.25=0 | | K/-3-2=-20 | | 11=-5k-2 | | 17/13=x/5 | | 5w-3w=39 | | C=70y+35 | | 12x^4y+18x^3y-24/6x^2y | | 8+3(2x-1)-(x+6)=-4 | | (4x+5)/2x=4 | | 26.6x+21.7-17.2x-35.8= | | 4xY+4=6xY | | 6x-15=x-8 | | 0.5(460+-0.6y)+0.3y=2(450+-0.5y)+1y | | 6x-24=42 | | 15-(4m-5)= | | 0.5(460+-0.6y)+0.3y=0 | | 12-(5x+8)-(8x-12)=14x-25-(3x-8)+(7x+2) | | 7x-9-8x+3=6x-7x-9 | | B+3=14 | | 1/9x=1/3 | | -3(-x+7)=12 | | k-52/6=5 | | f(-1)=-4x+2 | | 5=p+20/10 | | -11=7(p+24)-46 | | 9(x-8)-(7-9x)=17x | | 2(4x-11)=8x-22 | | f(-1)=-4+2 |